Macrochaete gen. nov. (Nostocales, Cyanobacteria), a taxon morphologically and molecularly distinct from Calothrix - Gómez, E. B.; Johansen, J. R.; Kaštovský, J.; Bohunická, M. (Markéta); Čapková, K. (Kateřina) (Journal of Phycology, 2016)
Macrochaete gen. nov. is a freshwater taxon sister to the Calothrix lineages but clearly separated from Rivularia . The species in this genus differ morphologically from Calothrix by their ability to produce two heteromorphic basal heterocytes and specific secondary structures of the 16S–23S ITS. We recognize three species: M. psychrophila (type species) from cold environments (high mountains, Antarctica), M. santannae from wet walls of subtropical South America, and M. lichenoides, a phycobiont of lichens from Europe.